K.H. Tubagus Ahmad Bakri Sempur’s Theological Thinking and Its Implications in Mashlahah Al-Islamiyyah Fi Ihkami Al-Tawhidiyyah - Kosasih, Ade; Mahdi, Sutiono; Fahrullah, Tb. Ace (Interdisciplinary Social Studies, 2022)
K.H. Tubagus Ahmad Bakri (died 1975) was a cleric in Sempur Village, Plered District, Purwakarta Regency, West Java. One form of his legacy is in the form of written works known as "nuqilan" or adaptations. One of them is Mashlahah Al-`Islamiyyah Fi `Ihkami Al-Tawhidiyyah (MIFIT) which specifically reveals thoughts on theological aspects in Islam. Uncovering patterns of theological thinking and religious teachings that can be applied in the lives of rural communities. This research uses the reception method, which is a critical study of the text and revealing the meanings contained in it. It is a qualitative method in whihch every sentence contained in the text is interpreted and connected with the reality of its implementation in everyday life in order to set an example to the audience, both students and society. The philological and textological studies of MIFIT critically produced the model of theological thinking that is very Ahlussunnah-centric by revealing the arguments of the Qur'an and the Prophet's Hadith as well as several Sunni scholars from the Middle East and the Indonesian Archipelago. The implications are at the level of practice of religious teachings in life which tend to be exclusive even though they prioritize tolerance.